Reduced models for the maximum vertical force in a tokamak device - G. Pautasso; E. Fable; the ASDEX Upgrade Team (Nuclear Fusion)
A formula was suggested in Miyamoto et al (2011 Plasma Phys. Control. Fusion 53 082001) to calculate the total maximum vertical force due to a vertical displacement event in a tokamak device without modeling the whole phenomenon. This formula is of interest because it would allow, if correct, to dimension the vessel and its supports during the conceptual design of a new device without having to use numerical codes for detailed simulations. The validation of the formula against ASDEX Upgrade measurements is not successful and the limiting assumption made to derive the formula is discussed. An alternative reduced model for the ASDEX Upgrade maximum vertical force is suggested.